(3HMhK YdejI eMceIs - (3YjO GMeO(B, (3GHh HcQs ((3YeGf(B:s (3OGQ UaGA(B,s, 2010)
(3JMdjd GMUGFj ebGQf ebGQf deYOdGJ JMejdGJ bSW GdJGejf Ydi GdMjGI aj GdShb GdeUQj , OhQ gjFI GdGTQGa h GdQbGHI Ydi GdJCejf aj JaYjd GdJRGe TQcGJ GdJCejf HJWHjb eHGOF h BdjGJ MhceI GdTQcGJ , fehPL QjGVj dJbOjQ GTJQGcGJ fXGe GdJCejfGJ GdGLJeGYjI aj eUQ aj Xd eYOd GdYGFO Ydi GdGSJKeGQh GdJVNe , fhePL cej deMOOGJ GdcaGAI GdeGdjI aj GdJCejf Ydi GdMjGI (B: (3OQGSI JWHjbjI Ydi TQcGJ GdJGejf GdeUQjI , JSYjQ GdJGejf GdGdRGej Ydi GdeQcHGJ habG dOQLI GdNWhQI aj VhA GdJMdjd Gdcej deDTQGJ GdMhGOK GdeQhQjI (B: (3OQGSI JWHjbjI Ydi Shb GdJGejf GdGQOfj , GSJQGJjLjI GOGQI GdeNGWQ GdeGdjI aj GdHfhc GdJLGQjI (B: (3OQGSI JMdjdjI ef efXhQ JGejfj eY GdGTGQI Gdi GdJLQHI GdeUQjI aj GOGQI eNGWQ GdJTZjd(B.s
Keywords: (3GdJCejf (B- (3GdHfhcs; (3GdJCejf(B- (3eUQs; (3HMhKs